Accounting System Design For Paradise Homestay - Angelin Angelin; Kennardi Tanujaya (Universitas Internasional Batam, 2023)
The system design is made to facilitate the recording transaction process at Paradise Homestay. Paradise Homestay is a business engaged in the hospitality sector which is located in Batam City. The accounting system at Paradise Homestay is done manually using Microsoft Excel, so that monthly reports must also be inputted manually which will take time to prepare. The survey method was carried out at business locations with criteria according to the requirements and the interview method was carried out with business representatives for their availability to contribute to the implementation of community service as well as interviews around the business. Paradise Homestay will benefit in the form of a more effective and efficient accounting recording system. Then, it is also beneficial by helping save companies time and costs, minimize errors, and improve asset management and inventory management. Managers will also be assisted in making decisions with accurate reports. Recommendations that can be made for further community service in helping micro-enterprises, such as helping to explain knowledge about how to operate a business both in management and finance.